High-efficiency microcrystalline silicon single-junction solar cells - Hänni, Simon; Bugnon, Grégory; Parascandolo, Gaetano; Boccard, Mathieu; Escarré, Jordi; Despeisse, Matthieu; Meillaud, Fanny; Ballif, Christophe (Progress in photovoltaics, 2013)
ABSTRACT This short communication highlights our latest results towards high‐efficiency microcrystalline silicon single‐junction solar cells. By combining adequate cell design with high‐quality material, a new world record efficiency was achieved for single‐junction microcrystalline silicon solar cell, with a conversion efficiency of 10.69%, independently confirmed at ISE CalLab PV Cells. Such significant conversion efficiency could be achieved with only 1.8 µm of Si. Copyright © 2013 John Wiley & Sons, Ltd. This short communication highlights our latest results towards high‐efficiency microcrystalline silicon single‐junction solar cells. By combining adequate cell design with high‐quality material, a new world record efficiency was achieved, with a conversion efficiency of 10.69%, independently confirmed at ISE CalLab PV Cells. Such significant conversion efficiency could be achieved with only 1.8µm of Si.